The effect of channel innovation knowledge management on competitive advantage: a dual-path model. Issue 2 (2nd April 2020) - Im, Subin; Kim, Stephen K.; Bond, Edward U.
ABSTRACT: Drawing on organizational learning theory, we integrate channels and NPD perspectives to address whether NPD teams can acquire innovation knowledge from channel partners and apply it to gain competitive advantage. Structural equation modeling using a sample of 205 product managers in U.S. high-technology manufacturing firms illustrates organizational ambidexterity that yields competitive advantage through an exploratory route from product novelty and new market accessibility to market pioneering and an exploitative route from product meaningfulness and channel operation efficiency to product quality superiority. We further develop new measures of channel innovation knowledge acquisition capabilities, channel innovation knowledge application capabilities, and market pioneering.